2004
DOI: 10.2746/0425164044890580
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of superficial digital flexor tendonitis and suspensory desmitis in Japanese Thoroughbred flat racehorses in 1999

Abstract: Summary Reasons for performing study: Overstrain injuries to the superficial digital flexor tendon (SDFT) and suspensory ligament (SL) are among the most common musculoskeletal injuries which contribute to the considerable wastage of racing Thoroughbreds. Many epidemiological studies have demonstrated the prevalence of and risk factors for tendon injury when racing but have not included those injuries sustained during training. However, since tendon injury during training is seen commonly in clinical practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
126
0
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 16 publications
6
126
0
12
Order By: Relevance
“…According to our results the positive effect of the application of PRP was registered not only in cases with acute injury but also in the chronic as well, which was similar to the results of Sutter et al (2004) who recommended application 30 days after the initial injury. Kasashima et al (2004) showed that there was an increase in the incidence of SDFT injury in racing horses from the age of two. They found that the most risky category is the five year old horses and that the probability of injury is three times higher than in two year old racing Thoroughbreds.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results the positive effect of the application of PRP was registered not only in cases with acute injury but also in the chronic as well, which was similar to the results of Sutter et al (2004) who recommended application 30 days after the initial injury. Kasashima et al (2004) showed that there was an increase in the incidence of SDFT injury in racing horses from the age of two. They found that the most risky category is the five year old horses and that the probability of injury is three times higher than in two year old racing Thoroughbreds.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the prevalence of Achilles injury is reported as 3% in the general population under 45 years of age [22], increasing to 15-56% in elite athletes, depending on the type of sport undertaken [22,23]. Injury to the SDFT in athletic horses is also common, with SDFT pathology reported in 11-24% of thoroughbred racehorses [24,25] and shows a similar initiation and progression to human Achilles tendinopathy [26,27]. Further, tendons become more prone to injury with increasing age, with regards to both the human Achilles [22,28] and equine SDFT [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The most common strain-induced injuries in horses are believed to be preceded by a phase of degeneration (Smith and Goodship 2004). Therefore prevalence of tendonitis increases with age, as shown by Kasashima et al (2004), Perkins et al (2005), Lam et al (2007).…”
Section: Introductionmentioning
confidence: 99%